STEM NECROSIS DISEASE RESISTANCE IN EXOTIC POTATO GERMPLASM - Somani, A. K. (Potato Journal, 2013)
Over 3 seasons, 271 exotic potato germplasm accessions from 21 countries were screened against stem necrosis disease caused by groundnut bud necrosis virus at the Central Potato Research Station, Gwalior (Madhya Pradesh)– a natural hot spot for the disease in early planted potatoes. Based on the average disease incidence and disease index, 46 accessions were found to be highly resistant, 62 resistant, 91 moderately resistant, 52 susceptible and 20 highly susceptible. Many of the highly resistant or resistant accessions were improved types and therefore can be used in potato breeding programme for developing varieties suitable for early production in stem necrosis prone areas of the Central and Western plains of India.